2016
DOI: 10.1016/j.jpeds.2015.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Does Not Influence Fracture Risk in Young Patients with Type 1 Diabetes

Abstract: Objectives To examine the risk of any fractures in patients with both type 1 diabetes (T1D) and celiac disease (CD) vs patients with T1D only. Study design We performed a population-based cohort study. We defined T1D as individuals aged ≤30 years who had a diagnosis of diabetes recorded in the Swedish National Patient Register between 1964–2009. Individuals with CD were identified through biopsy report data between 1969–2008 from any of Sweden’s 28 pathology departments. Some 958 individuals had both T1D and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…(18,44) Even in children with T1D, one study did not find an association between celiac disease and fracture risk. (45) In the present study, we could confirm that children and young adults with T1D and concomitant celiac disease have higher odds for fractures, especially prepubertal, and therefore at least the combination of these two diseases is associated with fracture risk. Unfortunately, we were not able to investigate the vitamin D status, but vitamin D deficiency could be a reason for the higher odds of fractures in individual with celiac disease.…”
Section: Discussionsupporting
confidence: 66%
“…(18,44) Even in children with T1D, one study did not find an association between celiac disease and fracture risk. (45) In the present study, we could confirm that children and young adults with T1D and concomitant celiac disease have higher odds for fractures, especially prepubertal, and therefore at least the combination of these two diseases is associated with fracture risk. Unfortunately, we were not able to investigate the vitamin D status, but vitamin D deficiency could be a reason for the higher odds of fractures in individual with celiac disease.…”
Section: Discussionsupporting
confidence: 66%
“…In another study, patients with T1D who developed CD revealed no increase in complication rate in comparison to their counterparts without CD (73, 74). Accordingly, diagnosis of CD in the context of T1D showed no significant impact on HbA1c levels in another study (75).…”
Section: Resultsmentioning
confidence: 89%
“…On the other hand, neither nutritional status, nor life quality of children with concurrent CD and T1D were different compared to individuals with T1D alone ( 72 ). In another study, patients with T1D who developed CD revealed no increase in complication rate in comparison to their counterparts without CD ( 73 , 74 ). Accordingly, diagnosis of CD in the context of T1D showed no significant impact on HbA1c levels in another study ( 75 ).…”
Section: Resultsmentioning
confidence: 89%
“…Studies examining fracture outcomes in adults with T1DM + CD are scarce. A prospective cohort study of over 5000 Swedish patients with T1DM did not demonstrate an increased risk of fracture in those with concomitant CD, compared with T1DM alone . However, there were several limitations of the study, including the large patient age range (4 to 71 years old) incomplete reporting of fractures and lack of information on glycaemic control and adherence to a GFD.…”
Section: Discussionmentioning
confidence: 91%
“…As T1DM and CD are both independently associated with bone fragility and fracture risk, this may be additive in T1DM + CD. Few studies have evaluated bone health in those with T1DM + CD, with some studies suggesting a negative impact on bone mineral density (BMD), whereas a large cohort study did not demonstrate increased fracture risk . These studies were primarily conducted in children, and extrapolation of results to an adult population is potentially inappropriate.…”
Section: Introductionmentioning
confidence: 99%